Electrochemical production of sustainable hydrocarbon fuels from CO2 co-electrolysis in eutectic molten melts - Al-Juboori, Ossama; Sher, Farooq; Khalid, Ushna; Niazi, Muhammad Bilal Khan; Chen, George Z. (American Chemical Society, 2020)
Because of the heavy reliance of people on limited fossil fuels as energy resources, global warming has increased to severe levels because of huge CO2 emission into the atmosphere. To mitigate this situation, a green method is presented here for the conversion of CO2/H2O into sustainable hydrocarbon fuels via electrolysis in eutectic molten salts [(KCl-LiCl; 41:59 mol %), (LiOH-NaOH; 27:73 mol %), (KOH-NaOH; 50:50 mol %), and (Li2CO3-Na2CO3-K2CO3; 43.5:31.5:25 mol %)] under the conditions of 1.5-2 V and 225-475 °C depending on the molten electrolyte used. Gas chromatography (GC) and GC-mass spectrometry (MS) techniques were employed to analyze the content of gaseous products. The electrolysis results in hydrocarbon production with maximum 59.30, 87.70, and 99% Faraday efficiencies in the case of molten chloride, molten hydroxide, and molten carbonate electrolytes under the temperatures of 375, 275, and 425 °C, respectively. GC with a flame-ionization detector and a thermal conductivity detector and GC-MS analysis confirmed that H2 and CH4 were the main products in the case of molten chlorides and hydroxides at an applied voltage of 2 V, while longer-chain hydrocarbons (>C1) were obtained only in molten carbonates at 1.5 V. In this way, electricity is transformed into chemical energy. The heating values obtained from the produced hydrocarbon fuels are satisfactory for further application. The practice of using molten salts could be a promising and encouraging technology for further fundamental investigation of sustainable hydrocarbon fuel formation with more product concentrations because of their fast electrolytic conversion rate without the use of a catalyst.